SAT-733 Improving the Diagnosis, Treatment, and Prevention of Endocrine Diseases Through Accurate and Reliable Laboratory Measurements with CDC’s Clinical Standardization Programs - Sugahara, Otoe (J Endocr Soc, 2020)
Laboratory measurements are critical for the correct diagnosis and treatment of patients as well as in the investigation of chronic diseases such as hypogonadism, PCOS, and bone-and kidney-related diseases. Inaccurate measurements can lead to misclassification of patients and incorrect treatment. Furthermore, the effective use of research findings in patient care is prevented. The CDC Clinical Standardization Programs (CDC CSP) assess the analytical performance of assays against performance goals defined by clinical and medical organizations. The CDC CSP assist with assay calibration, the certification of analytical performance, and the monitoring of analytical performance during the measurement of patient and/or study samples. CDC CSP have programs in place for the calibration and certification of commercial assays and laboratory developed tests (LDTs) for total testosterone (TT), estradiol (E2), vitamin D (VD), free thyroxine (FT4), total cholesterol (TC), total glycerides (TG), HDL-cholesterol (HDL-C), and LDL-cholesterol (LDL-C). The programs available for monitoring analytical performance during routine testing include TT, VD, TC, TG, HDL-C, apolipoprotein AI and B. CDC CSP also support accuracy-based external quality assurance surveys such as those offered by the College of American Pathologists. Enrollment of assays and LDTs in CDC’s certification programs has resulted in improvements in calibration accuracy; i.e. the absolute mean bias of assays participating in the CDC Vitamin D Standardization Certification Program was well below the allowable bias of 5% each year. Assays standardized in CDC’s certification programs also demonstrated higher accuracy in routine patient testing; i.e. CDC VD certified assays have a lower bias compared to non-certified assays. Similar observations were made with assays certified in the CDC’s program for TT. Monitoring data over the past 10 years from the CDC Lipid Standardization Program indicated that the majority of TC measurements performed in routine testing were consistently within the recommended bias limits of ±3%. CDC CSP continue to improve the analytical performance of assays by addressing measurement bias caused by factors other than incorrect calibration such as interfering compounds. The programs are responding to new clinical and public health needs with the addition of new analytes such as PTH and glucose. The CDC CSP support projects aiming at establishing reference intervals and other research studies. The CDC CSP work with stakeholders, such as the Partnership for the Accurate Testing of Hormones and the Endocrine Society, to educate the clinical and laboratory communities about the importance of using standardized assays in patient care, research, and public health. References: Partnership for Accurate Hormone Testing (PATH). www.hormoneassays.org. College of American Pathologists (CAP). www.cap.org.